Synthesis, Spectral and QSAR Studies of Danazol-Carbamazepine Conjugate - Lauro, Figueroa-Valverde; Francisco, Diaz-Cedillo; Maria, Lopez-Ramos; Elodia, Garcia-Cervera (Asian Journal of Chemistry, 2010)
In this work, two danazol-carbamazepine conjugate was synthesized and characterized by spectroscopy and spectral analyses. In order to characterize the structural chemical requirements of danazol-carbamazepine conjugate, several parameters such as log P, p, Rm and Vm, Pc and St were evaluated. The results showed an increase in the values of log P for danazol-carbamazepine conjugate in comparison with danazol. The danazol-carbamazepine conjugate showed an increase in the values of p, Rm and Vm, Pc and Stwith respect to danazol. In conclusion, all data suggest a relationship of the physicochemical descriptors evaluated with degree of lipophilicity from the danazol-carbamazepine conjugate.